Pemberdayaan Masyarakat Pada Kelompok Jago Karah Farm Jaya Utama Melalui Budidaya Peternakan Ayam di Kelurahan Karah Kota Surabaya - Istiqomah, Nur Faizatul; Rahaju, Tjitjik (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Empowerment in urban communities is a series of activities to build communities and improve the welfare of living standards by considering potential and needs. The Jago Karah Farm Jaya Utama Group was formed by the Karah Village to become an empowerment agent through innovation in chicken farming. The study aims to describe community empowerment in the Jago Karah Farm Jaya Utama Group and is designed using a qualitative descriptive approach. The focus of the study is the empowerment of change agents by Sulistiyani (2017), including Context, Input, Process, Output, and Outcome. Data were collected through interviews, observations, and documentation, then analyzed by data reduction, data presentation, and drawing conclusions. The results of this study indicate that community empowerment has been carried out by urban community groups through Jago Karah Farm Jaya Utama. Activities are based on village decrees and have a management structure. During empowerment, there are parties who play a role, efforts to utilize assistance, to product sales. However, there are obstacles such as low community interest, lack of management/managerial skills in chicken farming, limited facilities and infrastructure, and minimal budget support.